2021
DOI: 10.1007/s10570-021-04316-5
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of polyurethane and zirconium carbide coated cotton yarn

Abstract: In this work, polyurethane/zirconium carbide was coated on the surface of cotton ply yarn by sizing method. The effects of ZrC and PU concentration on the photothermal efficiency were studied. The results showed that when the concentration of zirconium carbide and polyurethane was 4 wt% and 6 wt% respectively, the infrared photothermal conversion performance of the composite yarn was the best, and its surface temperature increased from 22.1 °C to 77.3 °C after 5 min irradiation of IR lamp. The obtained composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…The results reveal that the MXene has been coated on the cotton fiber surface successfully. 35,53 The MCSY has a typical twisted yarn surface (Figure 1c) with a core−sheath (spandex yarn-Ti 3 C 2 T x /cotton) structure (Figure 1d). The cross section also shows a typical twisted structure of the yarn, which tightly covers MXene nanoparticles and prevents them from leakage.…”
Section: Resultsmentioning
confidence: 99%
“…The results reveal that the MXene has been coated on the cotton fiber surface successfully. 35,53 The MCSY has a typical twisted yarn surface (Figure 1c) with a core−sheath (spandex yarn-Ti 3 C 2 T x /cotton) structure (Figure 1d). The cross section also shows a typical twisted structure of the yarn, which tightly covers MXene nanoparticles and prevents them from leakage.…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that the quaternary ammonium cation could improve the liquid dispersion and stability of starch particles, which was mainly due to the function of the enhanced electrostatic repulsion among the starch chains. 41 Test effect of yarn performance…”
Section: Performance Analysis Of Sizingmentioning
confidence: 99%